Evaluation method for Green jack-up drilling platform design scheme based on improved grey correlation analysis. (April 2019) - Yunlong, Wang; Kai, Li; Guan, Guan; Yanyun, Yu; Fei, Liu
Highlights: Under the low-carbon economy it is important for green jack-up drilling platform (GJDP) design to select the optimum design scheme from the feasible schemes. This paper presents an evaluation method for GJDP design scheme based on the improved grey correlation analysis (IGCA). The evaluation index system for GJDP has been proposed which includes 3 factors: advanced technology, economic feasibility and environmental coordination, as well as 13 sub-indices. A multi-objective combinatorial optimization model is established by using IGCA, in which the analysis hierarchy process (AHP) is used to obtain the weight values of the indices. Abstract: This paper presents an evaluation method for green jack-up drilling platform(GJDP) design scheme based on the improved grey correlation analysis(IGCA). Under the situation of the low-carbon economy it is important and complicated for jack-up drilling platform design to select the optimum design scheme from the feasible schemes. In this paper, the evaluation index system for GJDP has been proposed which includes 3 factors: advanced technology, economic feasibility and environmental coordination, as well as 13 sub-indices. At the same time, a multi-objective combinatorial optimization model is established by using IGCA, in which the analysis hierarchy process (AHP) is used to obtain the weight values of the indices. The IGCA method is fully considered the connection of the indices reflecting the objective true nature of the things, and the subjective interest of the platform owner and the needs of the designer. This research can not only conduct to green design of jack-up drilling platform, but also can contribute to the development, popularization and application of low-carbon technology on offshore platform. Finally, the case study results demonstrate the feasibility and efficiency of the proposed evaluation method.